Usability And Cognitive Load Evaluation of The Threads Interface Using The System Usability Scale (SUS) And NASA-TLX Methods - Kifatul Hasna Tria Widyarsi; Yayak Kartika Sari; Taufiq Agung Cahyono (International Journal of Science and Environment (IJSE), 2026)
The rapid evolution of social media interfaces has reshaped how users consume digital information, and interface complexity is known to affect both ease of use and the mental effort users must invest. This study examines the level of usability and cognitive load of the Threads interface and the relationship between the two constructs, using a quantitative descriptive-correlational approach. An online questionnaire was distributed to 200 students of Universitas Bhinneka PGRI Tulungagung selected through purposive sampling. Usability was measured with the System Usability Scale (SUS) and cognitive load with the NASA Task Load Index (NASA-TLX); data were processed in IBM SPSS. All instruments were valid and reliable, with Cronbach's Alpha values of 0.728 (SUS) and 0.786 (NASA-TLX). The mean SUS score was 70.0875, placing Threads in the "Good" category, while the mean NASA-TLX score of 58.83 indicated a moderate level of cognitive load. A Pearson correlation coefficient of 0.474 (p = 0.000) and a simple linear regression equation of Y = 0.735 + 0.521X, with an R Square of 0.225, showed that usability contributed 22.5% to cognitive load. The findings indicate that Threads is reasonably user-friendly but still imposes a moderate cognitive burden on its users, and that this burden rises together with—rather than in opposition to—perceived usability.